Penerapan Kontrak Konstruksi Berbasis FIDIC dalam Proyek Jalan Tol Indonesia: Kajian Normatif terhadap Undang-Undang Jasa Konstruksi - Kodrat Insany Taqwim; Samián Samián; Dwi Edi Wibowo (Journal of Legal, Political, and Humanistic Inquiry, 2026)
The application of FIDIC-based construction contracts in Indonesian toll road projects raises significant normative questions regarding their compatibility with the national legal framework. This study employs a normative legal approach, combining statutory, conceptual, and comparative analyses to examine the alignment between FIDIC contractual structures and Indonesian Construction Services Law, the Civil Code, and the Arbitration Act. The findings indicate that while FIDIC reflects common law traditions emphasizing party autonomy, detailed risk allocation, and multi-tier dispute resolution mechanisms, Indonesian law imposes mandatory norms that limit contractual freedom in the interest of public order and legal certainty. Normative tensions primarily arise in clauses concerning risk distribution, variations, claims management, and the finality of dispute board and arbitral decisions. Nevertheless, these tensions do not render FIDIC inapplicable. Instead, adaptive drafting and systematic interpretation enable its integration within the Indonesian civil law system. Proper harmonization ensures that FIDIC contracts remain legally valid while supporting efficiency, certainty, and accountability in the delivery of strategic toll road infrastructure projects.